Digitization in nursing processes and the use of clinical decision support systems: do they improve perinatal indicators? - Asibe Özkan; Zehra Acar (BMC Pregnancy and Childbirth)
Abstract Background The increasing integration of digital technologies in healthcare has significantly enhanced the efficiency and quality of maternal and infant care services, with national and international bodies emphasizing the use of quality indicators to monitor and improve outcomes. Nursing plays a crucial role in this process, and the implementation of Clinical Decision Support Systems (CDSS) can further support nurses in providing high-quality care. Aim This study was carried out to determine the effects of digitization efforts and the CDSS, which were designed to improve perinatal indicators, on “safe childbirth checklist usage rates”, “rates of infants discharged following exclusive breastfeeding”, and “rates of mother–infant pairs starting skin–to–skin contact within one hour after delivery”. Methods The data for this retrospective, descriptive, and correlational study were collected between January and May 2024. The data, which were used to evaluate the perinatal indicators selected for the study and the effectiveness of digitization efforts and the CDSS designed for nursing, were obtained from indicator and log database records made in 2021–2023 in the Turkey Health Quality Indicators System (THQIS). Conclusion In the comparisons of the World Health Organization safe childbirth checklist usage rates, rates of infants discharged following exclusive breastfeeding, and rates of mother-infant pairs starting skin-to-skin contact within one hour after delivery according to the THQIS records in 2021, 2022, and 2023, the increase from 2021 to 2022 and the increase from the average of 2021–2022 to 2023 were found statistically significant. Digitization in nursing processes and the use of the CDSS were found to be highly beneficial for improving the perinatal indicators examined in the present study.